Site-specific seeding of Lewy pathology induces distinct pre-motor cellular and dendritic vulnerabilities in the cortex - Hammad F. Khan; Sayan Dutta; Alicia N. Scott; Shulan Xiao; Saumitra Yadav; Xiaoling Chen; Uma K. Aryal; Tamara L. Kinzer-Ursem; Jean-Christophe Rochet; Krishna Jayant (Nature Communications)
Abstract Circuit-based biomarkers distinguishing the gradual progression of Lewy pathology across synucleinopathies remain unknown. Here, we show that seeding of α-synuclein preformed fibrils in mouse dorsal striatum and motor cortex leads to distinct prodromal-phase cortical dysfunction across months. Our findings reveal that while both seeding sites had increased cortical pathology and hyperexcitability, distinct differences in electrophysiological and cellular ensemble patterns were crucial in distinguishing pathology spread between the two seeding sites. Notably, while beta-band spike-field-coherence reflected a significant increase beginning in Layer-5 and then spreading to Layer-2/3, the rate of entrainment and the propensity of stochastic beta-burst dynamics was markedly seeding location-specific. This beta dysfunction was accompanied by gradual superficial excitatory ensemble instability following cortical, but not striatal, preformed fibrils injection. We reveal a link between Layer-5 dendritic vulnerabilities and translaminar beta event dysfunction, which could be used to differentiate symptomatically similar synucleinopathies.